The influence of time of day on disruptive behaviours in middle school students during physical education classes - Bouzid, Mohamed Sami; Melki, Hassan; Racil, Ghazi; Hawani, Aymen; Hammoudi, Sabra; Rezgani, Youssef; Padulo, Johnny (Frontiers in Sports and Active Living, 2025)
IntroductionUnderstanding the factors influencing disruptive behaviour (DB) in Physical Education (PE) is essential for optimizing learning environments and student engagement. The aim of this study was to measure the frequency of DB in PE at two different times of the day, morning and afternoon, over an eight-week period.MethodsOne hundred thirty-seven male students participated in the study, with a mean age of 13.63 ± 0.7 years and PE experience of 5.7 ± 0.3 years. The Disciplinary Incidents Observing System (DIOS) was used to measure the frequency of DB occurrences during PE sessions.ResultsA significant difference was found in the average frequency of DBs observed between morning and afternoon sessions (p = 0.008 < 0.05). A total of 160 DBs were recorded during morning sessions, averaging 40 DBs per session or 0.8 DBs per minute. In contrast, 97 DBs were observed during afternoon sessions, averaging 24.25 DBs per session or 0.485 DBs per minute. These results suggest that physical activity in afternoon PE sessions is likely to significantly reduce the incidence of DBs.ConclusionThe findings of this study could serve as a valuable reference for decision-makers in organizing PE schedules, particularly in schools classified as “at risk”, where the prevalence of violence and incivility is above average.